Energy-Aware Adaptive Four Thresholds Technique for Optimal Virtual Machine Placement - A. R. Mohazabiyeh; K. H. Amirizadeh (Institute of Advanced Engineering and Science, 2018)
With the increasing expansion of cloud data centers and the demand for cloud services, one of the major problems facing these data centers is the “increasing growth in energy consumption